Variação da renda e participação da mulher no mercado de trabalho: o desenvolvimento importa? - Galucio, Thays Balieiro (Brasil, 2022)
After the World Wars, women’s participation in the labor market began to grow and change in terms of their role in society, starting not only to exercise a domestic function but also their importance to the economy of a country. The present work sought to analyze, among the countries collected, the participation of women in the labor market among the sectors of the economy and the wage inequality between men and women. Thus, the variables used were women’s and men’s income, GDP (US$), GDP per capita (US$), female and male participation in activities such as agriculture, industry and service, degree of economic freedom, Human Development Index, and also the Gender Inequality Index. Through the applications of Chow, Breusch-Pagan, and Hausman tests, it is possible to verify which of the three models would be suitable to perform the analyses, among them are: Pooled, Fixed, or Random Effects. The results show the lower women’s income when compared to the men’s income and the female insertion among the smaller sectors in industry and agriculture, however, the service activity with more participation of them in this sector. In the countries with a high HDI, female wages tend to be higher than those of men. Women’s income related to the degree of economic freedom increases in more economically liberal countries.